2012
DOI: 10.1016/j.mito.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of mitochondrial channels in cancer, ischemia–reperfusion injury, and neurodegeneration

Abstract: Mitochondria communicate with the rest of the cell through channels located in their inner and outer membranes. Most of the time, the message is encoded by the flow of anions and cations e.g., through VDAC and PTP, respectively. However, proteins are also both imported and exported across the mitochondrial membranes e.g, through TOM and MAC, respectively. Transport through mitochondrial channels is exquisitely regulated and controls a myriad of processes; from energy production to cell death. Here, we examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 160 publications
2
17
0
Order By: Relevance
“…VDAC is located in the outer mitochondrial membrane, which provides transport pathways for respiratory chain substrates required for oxidative phosphorylation (21,25,33,44). Our results are supported by results from other studies (33,44). Furthermore, we found that protein levels of complex V subunit-␣, located on the inner mitochondrial membrane, were significantly increased after ischemia-reperfusion in ipsilateral MCAs compared with control and contralateral MCAs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…VDAC is located in the outer mitochondrial membrane, which provides transport pathways for respiratory chain substrates required for oxidative phosphorylation (21,25,33,44). Our results are supported by results from other studies (33,44). Furthermore, we found that protein levels of complex V subunit-␣, located on the inner mitochondrial membrane, were significantly increased after ischemia-reperfusion in ipsilateral MCAs compared with control and contralateral MCAs.…”
Section: Discussionsupporting
confidence: 90%
“…First, the expression level of highly conserved VDAC, one of the major proteins in mitochondria-mediated apoptosis, was increased in ipsilateral MCAs compared with contralateral and control MCAs. VDAC is located in the outer mitochondrial membrane, which provides transport pathways for respiratory chain substrates required for oxidative phosphorylation (21,25,33,44). Our results are supported by results from other studies (33,44).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, conductance of VDAC in living cell needs to be studied in details in order to better understand VDAC function in vivo and effect of VDAC modulators in therapy, including the isoform specificity. However, as mentioned by [76], it is still not clear whether VDAC is intrinsically open in living cells as suggested by the low permeability barrier of the mitochondrial outer membrane or is closed. Therefore, answering the question appears to be important for development of new therapeutic interventions based on VDAC modulators.…”
Section: Vdac As a Versatile Proteinmentioning
confidence: 99%
“…Mitochondrial channels also control cell survival and death. These channels mainly include mPTP, mitochondrial porin or voltage-dependent anion-selective channel (VDAC), adenine nucleotide translocase (ANT), and protein import translocases (TOM, TIM23, and TIM22) in outer and inner membranes (Peixoto et al, 2012). A fully open VDAC allows the flux of metabolites, including ATP, ADP, Ca 2+ , K + , and Na + , across the outer membrane (Colombini, 2012).…”
Section: Function Of Mitochondrial Channels In Mitochondrion-dependenmentioning
confidence: 99%